THE CORRELATION BETWEEN VOCABULARY MASTERY AND READING COMPREHENSION OF THE ELEVENTH GRADE STUDENTS OF SMA NEGERI 1 INDRALAYA - Nita Ria; Novi Perdawati (Universitas Tridinanti Palembang, 2021)
Vocabulary mastery is an individual's skill in using words of a language. Reading comprehension is the act of understanding of a text. Reader can understand the meaning, main idea, topic and summary of the text by mastering vocabulary. The objectives of this study were to find out whether or not there was a significant correlation between vocabulary mastery and reading comprehension of the eleventh grade students of SMA Negeri 1 Indralaya and to find out in how much the vocabulary mastery contributes toward reading comprehension of the eleventh grade students. This study used a correlational research design. This study involved 65 students as the sample chosen by using cluster random sampling technique. The data were collected by vocabulary mastery test and reading comprehension test. The techniques for analyzing the data were correlational analysis and regression analysis. The results of study found that there was a significant correlation between vocabulary mastery and reading comprehension of the eleventh-grade students since p-value (0.049) was lower than 0.05. Then, the rvalue was 0.245 that showed as weak or low correlation between vocabulary mastery and reading comprehension of the eleventh grade Students. Vocabulary mastery also gave contribution to reading comprehension as much as 6 %. Keywords: vocabulary mastery, reading comprehension, explanation text